(Un)Obtrusive Control in Emergent Networks: Examining Funding Agencies' Control Over Nonprofit Networks. (June 2017) - Doerfel, Marya L.; Atouba, Yannick; Harris, Jack L.
Nonprofit sector organizations tackle intractable problems by seeking support from external funding agencies, resulting in funders holding power through resource control. Nonprofits also access resources and coordinate activities through building networks with other nonprofits. Such networks have been viewed as emergent with an underlying assumption that the nonprofits determine when and with whom to partner. Given the power of funders, however, how much control do the nonprofits have in determining whether or not to partner? Document analysis of 83 application packets used by funders in the United States to collect and assess nonprofit suitability for funding shows significant differences between private- and public-sector control over nonprofits decisions to network. Unlike private-sector foundations, public-agency funding documents mandate awardees to network, which has practical and theoretical implications. Although the idea of building a network implies autonomous acts on the part of nonprofits, some are prone to hierarchical influences through grant-making policy.